Assessment of selected spatio-temporal gait parameters on subjects with pronated foot posture on the basis of measurements using OptoGait. A case-control study - Requelo-Rodríguez, Inmaculada; Castro-Méndez, Aurora; Jiménez-Cebrián, Ana María; González-Elena, María Luisa; Palomo-Toucedo, Inmaculada C.; Pabón-Carrasco, Manuel (MDPI, 2021)
Walking is part of daily life and in asymptomatic subjects it is relatively easy. The physiology of walking is complex and when this complex control system fails, the risk of falls increases. As a result, gait disorders have a major impact on the older adult population and have increased in frequency as a result of population aging. Therefore, the OptoGait sensor is intended to identify gait imbalances in pronating feet to try to prevent falling and injury by compensating for it with treatments that normalize such alteration. This study is intended to assess whether spatiotemporal alterations occur in the gait cycle in a young pronating population (cases) compared to a control group (non-pronating patients) analyzed with OptoGait. Method: a total of n = 142 participants consisting of n = 70 cases (pronators) and n = 72 healthy controls were studied by means of a 30 s treadmill program with a system of 96 OptoGait LED sensors. Results: Significant differences were found between the two groups and both feet in stride length and stride time, gait cycle duration and gait cadence (in all cases p < 0.05). Conclusions: pronating foot posture alters normal gait patterns measured by OptoGait; this finding presents imbalance in gait as an underlying factor. Prevention of this alteration could be considered in relation to its relationship to the risk of falling in future investigations.
Keywords: Locomoción; Pies - Lesiones y heridas; Telemedicina; Optogait; Caída; Índice de postura de pies; Marcha; Prevención; Pronación; Riesgo